2010
DOI: 10.1016/j.freeradbiomed.2010.10.461
|View full text |Cite
|
Sign up to set email alerts
|

Ohr (Organic hydroperoxide resistance protein) Possesses a Previously Undescribed Activity: Lipoyldependent Peroxidase

Abstract: The Ohr (organic hydroperoxide resistance) family of 15-kDa Cys-based, thiol-dependent peroxidases is central to the bacterial response to stress induced by organic hydroperoxides but not by hydrogen peroxide. Ohr has a unique three-dimensional structure and requires dithiols, but not monothiols, to support its activity. However, the physiological reducing system of Ohr has not yet been identified. Here we show that lipoylated enzymes present in the bacterial extracts of Xylella fastidiosa interacted physicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2016
2016
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…Sequence analysis revealed that the plasmid harbored a gene annotated as ohrA (vca1006), which is predicted to encode a putative organic hydroperoxide resistance protein. In other bacteria, OhrA has been shown to be a lipoyl-dependent peroxidase, reducing both inorganic and organic hydroperoxides to less toxic metabolites at its cysteine thiol (Lesniak et al, 2002;Cussiol et al, 2010). OhrA of V. cholerae is highly homologous to these well-studied OhrA proteins, and in particular contains two conserved cysteine residues (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Sequence analysis revealed that the plasmid harbored a gene annotated as ohrA (vca1006), which is predicted to encode a putative organic hydroperoxide resistance protein. In other bacteria, OhrA has been shown to be a lipoyl-dependent peroxidase, reducing both inorganic and organic hydroperoxides to less toxic metabolites at its cysteine thiol (Lesniak et al, 2002;Cussiol et al, 2010). OhrA of V. cholerae is highly homologous to these well-studied OhrA proteins, and in particular contains two conserved cysteine residues (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Inicialmente, os pré-inóculos das linhagens foram diluídos para DO600 0,05 em 500 mL de LB suplementado com ampicilina. As culturas foram então cultivadas a 37 ºC sob agitação de 250 rpm até ser atingida DO600 0,4 -0,6.Posteriormente, IPTG (IPTG -Isopropyl b-D-1-thiogalactopyranoside) foi adicionado aos cultivos (1 mM para His-ChuP; 0,5 mM para His-ChuS) e estes induzidos (37 ºC sob 250 rpm por 2 horas para His-ChuP; 20 ºC sob 60 rpm por 24 horas para His-ChuP)(CUSSIOL et al, 2010). Após indução, as culturas foram centrifugadas a 14000x g por 5 minutos a 4 ºC e os pellets obtidos foram ressuspendidos em água Milli-Q, centrifugados e armazenados a -20 ºC.…”
unclassified